Evolution of theories of mind - Erik Mohlin (Stockholm School of Economics, The Economic Research Institute (EFI), 2010)
This paper studies the evolution of peoples' models of how other people think - their theories of mind. First, this is formalized within the level-k model, which postulates a hierarchy of types, such that type k plays a k times iterated best response to the uniform distribution. It is found that, under plausible conditions, lower types co-exist with higher types. The results are extended to a model of learning, in which type k plays a k times iterated best response the average of past play. The model is also extended to allow for partial observability of the opponent's type.
Keywords: C72; C73; D01; D03; D83; 330; Theory of Mind; Depth of Reasoning; Evolution; Learning; Level-k; Fictitious Play; Cognitive Hierarchy; Evolutionäre Spieltheorie; Lernen; Intelligenz